Comparative evaluation by scanning confocal Raman spectroscopy and transmission electron microscopy of therapeutic effects of noble metal nanoparticles in experimental acute inflammation1. Issue 83 (9th September 2015) - Filip, Adriana; Potara, Monica; Florea, Adrian; Baldea, Ioana; Olteanu, Diana; Bolfa, Pompei; Clichici, Simona; David, Luminita; Moldovan, Bianca; Olenic, Liliana; Astilean, Simion
<x xml:space="preserve">Abstract</x> A test of Raman spectroscopy as a technique to diagnose inflammatory conditions and differentiate the effect of treatments with silver and gold nanoparticles conjugated with natural extracts compared with microscopy in experimental acute inflammation.